Flyback Cascaded Multilevel Inverter Based SHE-PWM Control for STATCOM Applications - Kah Haw Law; Wendy Pei Qin Ng; Wei Kitt Wong (Institute of Advanced Engineering and Science, 2017)
This paper presents the closed loop DC-DC flyback converter with multi-level cascaded H-bridge inverter (MCHI) for transformer-less static synchronous compensator (STATCOM) system. The STATCOM system is proposed to be controlled using decoupled dq vector control incorporating the new reactive current reference algorithm and multi-level selective harmonic elimination pulse width modulation (MSHEPWM) technique. This ensures transient performance enhancement as well as simpler control and modulation technique implementation for dynamic systems. As the proposed MSHEPWM solely depends on adjustable DC-link voltage levels, flyback converter is designed for that purpose to suit wider applications. In current work, a single phase five-levels CHI based STATCOM system incorporated with the aforementioned converters are presented to compensate the reactive power (VAR) at the point of common connection (PCC). The dynamic as well as the transient performances of the developed STATCOM control system and the proposed voltage closed loop control of each converter are investigated to meet different VAR demands at balanced loading conditions. Simulation studies are performed to verify the effectiveness and theoretical analysis of the approaches presented.